Perbandingan Tepung Porang (Amorphophallus Muelleri B.) Dan Ampas Wortel (Daucus Carota L.) Terhadap Karakteristik Topping Boba - Pramudita, Felicia Chessa; Wiadnyani, Anak Agung Istri Sri; Puspawati, Gusti Ayu Kadek Diah (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2024)
Boba drinks are beverages served with chewy tapioca-based toppings known as “boba”, “bubble”, or “pearl”. These toppings are high in sugar, calories, and carbohydrates but have low amounts of fiber and vitamins. Adding carrot pulp to “Caboom” (Carrot Boba Milk) toppings is expected to increase fiber and vitamin content. However, there's an issue with texture; the boba toppings aren’t achieving the desired chewiness and tends to crumble easily. Therefore, the addition of another ingredient is necessary, and porang ( Amorphophallus muelleri Blume ) flour is a suitable choice because it’s known for its ability to act as a gelling agent due to its glucomannan content. This research aimed to determine how the ratio of porang flour and carrot pulp affects the characteristics of boba toppings and determine the right ratio for achieving the best boba toppings characteristic. In this research, a completely randomized design was used, involving six treatment levels representing different ratios of porang flour and carrot pulp: 0:100, 25:75, 50:50, 75:25, and 100:0, replicated three times, resulting in a total of 15 experimental units. The collected data underwent analysis through ANOVA and followed by Duncan Multiple Range Test (DMRT). The results revealed that the comparison of porang flour and carrot pulp had a significant effect (P<0,05) on water content, ?-carotene content, hardness, and the hedonic ratings for attributes such as color, aroma, taste, texture, and overall acceptance. Among the different ratios considered, the comparison of 50% porang flour and 50% carrot pulp emerged as the best boba toppings characteristic with water content 68,5%, ?-carotene content 0,94%, hardness 1,65 N, the color is slightly like, the aroma is slightly like, the taste is like, the texture is like, overall acceptance is like, the total dietary fiber content 5,51%, and antioxidant activity 9,62%.